TREATMENT OF TRADITIONAL ETHANOL FERMENTATION WASTE WITH ELECTROLYSIS METHOD FOR DECREASING COD AND SULFIDE - Dimas Eko Saputro; Siti Fatimah (Indonesian Journal of Technology, Informatics and Science (IJTIS), 2021)
Ethanol is produced from molasses by a fermentation process. In Bekonang, ethanol manufacturingby a home-scale industry so the waste just thrown away in free water then pollution occurs both in rivers and in paddy fields. Ethanol waste has very high chemical oxygen demand (COD) and contain high sulfide. Electrolysis that use for reduce leves COD dan Sulfide with electricity as main source for direct current flowing  electricity (dc) to the anode and cathode. Electrolysis time 10, 15, 20, 25 and 30 minutes and voltage variation 5, 10 and 15 volt. Based on data obtained in the test COD obtained optimum levels of  284.5 mg/L from the initial content of  586 mg/L , at a time variation of 30 minutes and voltage 15 volt. The sulfide test obtained optimum levels of 0.0661 mg/L from the initial content of 0.305 mg/L, at time variation of 25 minutes and a voltage of 15 volt.